Concert of Asia: How the World Should Deal with the Rise of China - Wirawan, Rendy (Department of International Relations, Universitas Mulawarman, 2021)
As the China rise rapidly and aggressively, the world continues to be vulnerable due to the uncertain geopolitical environment and detrimental great powers gesture. This happens roughly at the global stage but more ominous to the regional politics in Asia Pacific. The region needs to spend more effort to deal with the rising China and somehow also required to alter the US primacy in global politics. To assure regional stability and security, this article proposes the model of the ‘concert of power’ inspired by the Concert of Europe to be carried out in Asia, precisely in Asia Pacific. The Concert of Asia enables more powers, great or mediocre, who are keys to the regional stability to perform checks and balances to one another, not only China itself. There are at least two great powers involve, China and the US. Also, there are few key players in the region that needs to be considered, not so powerful, but still have significant role, namely ASEAN and Japan. With this model, none of great powers could dominate the region and allowing states to secure themselves. Otherwise, great power rivalry is at stake.